Online Shopping Interest in Makassar City - Wardihan Sabar; Asrini Said (Universitas Islam Negeri Alauddin Makassar, 2022)
Mainstream online shopping through various shopping sites continues to increase in the variety of products offered. This study aims to determine the determinants of the level of demand for products offered online. This research is Quantitative Research with an explanatory approach. This research was conducted in Makassar City by involving 50 respondents randomly but with the criteria of having an online shopping experience. Data collection techniques using a questionnaire. Giving a score with a Likert Scale technique. The data analysis technique used is multiple linear regression with the help of E-Views version 9.0 software. The results showed that product quality), price, substitution price, and taste had a positive and significant effect on the demand for online products in Makassar City. Meanwhile, the price of substitute goods has no significant effect on the demand for online products in Makassar City. Indicators of Quality, Price, and Taste can be valuable inputs for online sellers to maintain and increase consumer confidence to be able to boost sales of their products.